2014
DOI: 10.1097/eja.0b013e328365ae49
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Aintree and Fastrach techniques for low-skill fibreoptic intubation in patients at risk of secondary cervical injury

Abstract: Fibreoptic intubation using the Aintree system was more successful than the Fastrach technique in our population of patients in a neutral position wearing a soft cervical collar. The differences in the time to successful intubation between the two groups are unlikely to be clinically relevant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 24 publications
1
9
0
1
Order By: Relevance
“…We found no significant difference in time to fibreoptic‐guided tracheal intubation between the two groups. These findings compare favourably with studies looking at fibreoptic‐guided tracheal intubation via other SADs (including the i‐gel) .…”
Section: Discussionsupporting
confidence: 70%
“…We found no significant difference in time to fibreoptic‐guided tracheal intubation between the two groups. These findings compare favourably with studies looking at fibreoptic‐guided tracheal intubation via other SADs (including the i‐gel) .…”
Section: Discussionsupporting
confidence: 70%
“…The iLMA has a stiff angled shank and a wide internal diameter for ETT insertion, as does the LMA Fastrach™. It is also shorter than other LMAs and has a stabiliser rod that pushes the ETT [14]. A previous study compared the efficacy of the iLMA with that of a combination of the AIC and classic LMA (cLMA) during insertion of a 7.0 mm ID ETT.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study compared the efficacy of the iLMA with that of a combination of the AIC and classic LMA (cLMA) during insertion of a 7.0 mm ID ETT. They reported that not only was iLMA insertion more difficult than cLMA, but it also resulted in a poor glottis view in 26% of cases, even after insertion [14]. Furthermore, the iLMA is less widely available than the cLMA [9] and has a steeper learning curve, hampering its routine use [18] Thus, the iLMA does not appear to improve upon the combination of the AIC and cLMA [14,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ainsi, en plus de permettre une intubation primaire, l'Aintree peut être utilisé pour l'échange de TET tout en étant positionné par fibroscopie. Comme il s'adapte au travers d'un dispositif supra-glottique, il peut également servir de guide à l'intubation trachéale tout en administrant de l'oxygène au patient[30][31][32]. Son développement a été intimement lié à la volonté de permettre une intubation assisté par la fibre optique, tout en gardant à tout moment un contrôle de la voie aérienne.…”
unclassified